A Novel Drug Resistance Mechanism: Genetic Loss of Xeroderma Pigmentosum Complementation Group C (XPC) Enhances Glycolysis-Mediated Drug Resistance in DLD-1 Colon Cancer Cells - Han, Yu; Qu, Yuan Qing; Mok, Simon Wing Fai; Chen, Juan; Xia, Cheng Lai; He, Hu Qiang; Li, Zheng; Zhang, Wei; Qiu, Cong Ling; Liu, Liang; Law, Betty Yuen Kwan; Wong, Vincent Kam Wai (Frontiers in Pharmacology, 2019)
The pro-apoptotic proteins BAX and BAK are critical regulatory factors constituting the apoptosis machinery. Downregulated expression of BAX and BAK in human colorectal cancer lead to chemotherapeutic failure and poor survival rate in patients. In this study, isogenic DLD-1 colon cancer cells and the BAX and BAK double knockout counterpart were used as the cellular model to investigate the role of BAX/BAK-associated signaling network and the corresponding downstream effects in the development of drug resistance. Our data suggested that DLD-1 colon cancer cells with BAX/BAK double-knockout were selectively resistant to a panel of FDA-approved drugs (27 out of 66), including etoposide. PCR array analysis for the transcriptional profiling of genes related to human cancer drug resistance validated the altered level of 12 genes (3 upregulated and 9 downregulated) in DLD-1 colon cancer cells lack of BAX and BAK expression. Amongst these genes, XPC responsible for DNA repairment and cellular respiration demonstrated the highest tolerance towards etoposide treatment accompanying upregulated glycolysis as revealed by metabolic stress assay in DLD-1 colon cancer cells deficient with XPC. Collectively, our findings provide insight into the search of novel therapeutic strategies and pharmacological targets to against cancer drug resistance genetically associated with BAX, BAK, and XPC, for improving the therapy of colorectal cancer via the glycolytic pathway.